Mentalization and criterion a of the alternative model for personality disorders: results from a clinical and nonclinical sample - Zettl, Max; Volkert, Jana; Vögele, Claus; Herpertz, Sabine; Kubera, Katharina Maria; Taubner, Svenja (Personality disorders, 2020)
Criterion A of the alternative model for the classification of personality disorders in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), introduced the Level of Personality Functioning Scale (LPFS), a dimensional model for the assessment of impairments in self and interpersonal functioning. The LPFS was developed based on a review of different measures of personality functioning, such as the Reflective Functioning Scale, a measure of mentalizing. This study investigated the empirical overlap between the LPFS and mentalization. The study sample included adult inpatients (n = 55) with a mental disorder and a healthy adult control group (n = 55). All participants were examined regarding the LPFS using the Semistructured Interview for Personality Functioning DSM-5; mentalizing was assessed with the Brief Reflective Functioning Interview and coded with the Reflective Functioning Scale. We used structural equation modeling to investigate the relationship between LPFS domains and mentalization. Correlation analysis was used to examine the agreement between interview-rated LPFS and self-report measures of personality dysfunction. All domains of the LPFS were significantly related to mentalizing. Interview-rated LPFS was significantly associated with self-reported personality dysfunction. The findings support the notion that the LPFS and mentalization share a strong conceptual and operational overlap by demonstrating that both constructs are empirically interrelated. The results yield further support for the validity of the LPFS as a dimensional model for the assessment of personality disorder severity. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Gesehen am 04.06.2020
Published online September 2, 2019